Cognitive architectures and brain: towards an unified theory of cognition (2011)
Cognitive architectures are defined as the group of essential components belonging to a system which allows the analysis of its cognitions and behaviors. The aim of this study is to review one of the most plausible cognitive architectures from the neuroanatomic perspective: The Adaptive Control of Thought-Rational (ACT-R) is a theory about how human mind works. Following an initial approach to its basic concepts its two computational levels are described, these are: a symbolic level , which includes declarative information; and a sub-symbolic level which is represented as a parallel set of processes. At the same time, architecture’s modules are related to brain’s functional neuroanatomy describing how cortico-striatal-thalamic circuit works